Mengembangkan Kemampuan Literasi Baca Tulis Anak Melalui Kegiatan One Word of The Day di TK Islam Al Azhar 29 BSB Semarang - Zulfa Dwi Aulia; Muslam; Mursid (Institut Agama Islam Negeri Madura, 2025)
Improving literacy skills in children is very important to do fro an early age. By instilling literacy skills from an early age, it will become an important capital for children in living their daily lives in the future. Literacy is also a foundation that will affect children’s social, emotional, and cognitive development. This study aims to determine the development of children’s literacy skills through one word of the day activities in group B Al Ghofar KB-TK Islam Al Azhar 29 BSB Semarang. This study uses a qualitative descriptive method, where the data collected are in the form of words, pictures, and not numbers. The data collection techniques used are observation, interviews, and documentation. The result of the study showed that one word of the day activities in group B Al Ghofar KB-TK Islam Al Azhar 29 BSB Semarang can improve children’s literacy skills, including: 1. Children who previously did not know letters began to understand letters, 2. Children who did not know syllables began to recognize words became accustomed to learing to compose words.